Metabolic medicine and surgery [ - Haverstick, Lisa P.; Nusbaum, Michael J.; Rothkopf, Michael M. (CRC Press, 2015)
"Health practitioners who deal with disease by attempting to restore normal metabolism are said to practice metabolic medicine. This book is intended to be the first comprehensive overview in the field of metabolic medicine, which is dedicated to controlling the epidemic of obesity and preventing obesity's consequences. It introduces metabolic medicine and surgery, and covers metabolic syndrome as an epidemic, metabolic approaches to diabetes and obesity, and metabolic management in chronic disease states"